Characteristics of the peroxisome proliferator activated receptor γ (PPARγ) ligand induced apoptosis in colon cancer cells. Issue 5 (1st May 2002) - Shimada, T; Kojima, K; Yoshiura, K; Hiraishi, H; Terano, A
Abstract : Background: Involvement of peroxisome proliferator activated receptor γ (PPARγ) in the growth response of colon cancer cells has been suggested. Aims: To investigate the characteristics of PPARγ induced apoptosis in colon cancer cells. Methods: The effects of ligands for each of the PPAR subtypes (α, δ, and γ) on DNA synthesis and cell viability were examined in HT-29 colon cancer cells. Modulation of apoptosis related gene expression by PPARγ ligands was screened with cDNA arrays, and the results were confirmed by quantitative reverse transcription-polymerase chain reaction (RT-PCR) analysis. Results: PPARα, PPARδ, and PPARγ were all expressed in HT-29 cells. PPARγ ligands, 15-deoxy-δ 12, 14 -prostaglandin J2 (15d-PGJ2 ) and troglitazone (TGZ), suppressed DNA synthesis of HT-29 cells whereas ligands for PPARα and PPARδ had no significant effects. Both 15d-PGJ2 and TGZ induced HT-29 cell death in a dose dependent manner which was associated with an increase in fragmented DNA and was sensitive to a caspase inhibitor. Among several genes selected by cDNA array screening, quantitative RT-PCR analysis confirmed downregulation of c-myc expression and upregulation of c-jun and gadd153 expression by 15d-PGJ2 and TGZ. PPARγ induced apoptosis was antagonised by the presence of serum in the culture medium, and interaction between PPARγ signalling and cell survival signalling through the phosphatidylinositol 3-kinase pathway was suggested. Conclusions: As c-myc is an important target gene of the adenomatous polyposis coli (APC)/β-catenin and/or APC/γ-catenin pathway, activation of PPARγ signalling appears to compensate for deregulated c-myc expression caused by mutated APC. The present results suggest the potential usefulness of PPARγ ligands for chemoprevention and treatment of colon cancers.